PENINGKATAN PENGETAHUAN MENGENAI P3K TERHADAP SISWA SD KELAS 5 - 6 DENGAN MEDIA E-BOOKCERITA BERGAMBAR - Putra, Fajar Alam; Sutrisno, Sutrisno; Sumarni, Rantiningsih; Prasmagiri, Bintang; Alya, Feriska Dwi (Universitas Mataram, 2025)
Clean and healthy living behavior should be instilled from an early age and can begin within the family and school environment. Health education for school-aged children can be facilitated through the School Health Program (UKS). One of the key factors for the success of the UKS program is the presence of First Aid Officers and health-related activities in schools. To establish a proper UKS room and provide trained First Aid Officers who are capable of serving as the first response team for health issues at SD N 01 Bugel. This community service activity was carried out by providing training on basic materials for First Aid Officers to enhance knowledge and skills related to clean and healthy living behaviors, as well as first aid for common health problems among students. The training for First Aid Officers contributed to promoting healthy living behaviors. The trained officers understood the correct procedures for handwashing, appropriate timing, and the importance of using clean running water. Student First Aid Officers were able to comprehend and practice first aid for health problems occurring at school. Providing training to First Aid Officers proved effective in delivering education that led to improved knowledge and a positive change in behavior.